Transcription factor AP-2β regulates the neurotransmitter phenotype and maturation of chromaffin cells - Hong, Seok Jong (2010)
During development, sympathetic neurons and chromaffin cells originate from bipotential sympathoadrenal (SA) progenitors arising from neural crests (NC) in the trunk regions. Recently, we showed that AP-2β, a member of the AP2 family, plays a critical role in the development of sympathetic neurons and locus coeruleus and their norepinephrine (NE) neurotransmitter phenotype. In the present study, we investigated the potential role of AP-2β in the development of NC-derived neuroendocrine chromaffin cells of the adrenal medulla and the epinephrine (EPI) phenotype determination. In support of its role in chromaffin cell development, AP-2β is prominently expressed in both embryonic and adult adrenal medulla. In adrenal chromaffin cells of the AP-2β(−/−) mouse, the expression levels of catecholamine biosynthesizing enzymes, dopamine β-hydroxylase (DBH) and phenylethanolamine-N-methyl-transferase (PNMT), as well as the SA-specific transcription factor, Phox2b, are significantly reduced compared to wild type. In addition, ultrastructural analysis demonstrated that formation of large secretory vesicles, a hallmark of differentiated chromaffin cells, is defective in AP-2β(−/−) mice. Furthermore, the level of EPI content is largely diminished (>80%) in the adrenal gland of AP-2β(−/−) mice. Chromatin immunoprecipitation (ChIP) assays of rat adrenal gland showed that AP-2β binds to the upstream promoter of the PNMT gene in vivo; strongly suggesting that it is a direct target gene. Overall, our data suggest that AP-2β plays critical roles in the epinephrine phenotype and maturation of adrenal chromaffin cells.